Physical and postural aspects of teachers during work activity. - Soares, Marcelo M.; Jacobs, Karen; Silva, Nilson RogÉrio da; Almeida, Maria Amélia (Work)
Studies indicate that teachers constitute a professional segment, in which the work characteristics and the demands originating from the act of teaching, favor the emergence of sickness, concerning physical or emotional aspects. The present work aimed to describe physical and postural aspects during the working activity of teachers. A total of 120 elementary school teachers (1st to 8th grade) took part in the survey. For data collection, a questionnaire was applied: it included personal and occupational information, perception of discomfort and being off work; physical strength activities; posture at work and physical conditioning activities. The average age of teachers of the present sample corresponds to 35,8 years. In relation to activities which generate more physical strength, the answer none of the activities was predominant with 30 answers; followed by writing on the board, standing up during the period of classes, explanation of the subjects, class elaboration, correction of homework and others. The area of the body with higher amount of occurrences and prevalent discomfort referred to the lower limbs and spinal cord. These data inform the necessity of investing in prevention programs for the teachers, in order to develop strategies into the organizational context and interventions at the work environment.